2008
DOI: 10.1103/physrevlett.100.047601
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in an Ising Chain Magnet

Abstract: We report discovery of collinear-magnetism-driven ferroelectricity in the Ising chain magnet Ca3Co2-xMn(x)O6 (x approximately 0.96). Neutron diffraction shows that Co2+ and Mn4+ ions alternating along the chains exhibit an up-up-down-down ( upward arrow upward arrow downward arrow downward arrow) magnetic order. The ferroelectricity results from the inversion symmetry breaking in the upward arrow upward arrow downward arrow downward arrow spin chain with an alternating charge order. Unlike in spiral magnetoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
420
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(441 citation statements)
references
References 27 publications
17
420
3
1
Order By: Relevance
“…Polarization may appear in collinear magnets as long as the magnetic order involves different magnetic atoms between which the exchange coupling varies. This is the case, for example, for Ca 3 CoMnO 6 , which consists of one-dimensional chains of Co and Mn [65]. The magnetic order distorts the bonds, thus breaking the space inversion symmetry and allowing for polarization to develop.…”
Section: Ii) Joint-order Multi-ferroics (Type Ii)mentioning
confidence: 99%
“…Polarization may appear in collinear magnets as long as the magnetic order involves different magnetic atoms between which the exchange coupling varies. This is the case, for example, for Ca 3 CoMnO 6 , which consists of one-dimensional chains of Co and Mn [65]. The magnetic order distorts the bonds, thus breaking the space inversion symmetry and allowing for polarization to develop.…”
Section: Ii) Joint-order Multi-ferroics (Type Ii)mentioning
confidence: 99%
“…The recent discovery of magnetic control of the electric polarization in manganite 2 has attracted significant attention in pure and applied science. The following large number of studies revealed three major microscopic scenarios to induce the electric polarization by the spin system 3 : spin current [4][5][6] , exchange striction 7,8 and spin-dependent p-d hybridization mechanisms [9][10][11] .…”
mentioning
confidence: 99%
“…A variety of such mechanisms have been proposed [6]: magneto-striction is the only allowed mechanism for acentric collinear structures, and is active in the Ising system Ca 3 (Co,Mn) 2 O 6 [7] and, most likely, in the commensurate phase of YMn 2 O 5 [8]. Most other "type-II" multiferroics are cycloidal magnets, where non-collinear spins are key ingredients in the context of the so-called spincurrent model [9,10].…”
mentioning
confidence: 99%